Tajdidun Nikah Sebagai Upaya Penguatan Keluarga Sakinah (Studi Kasus di Desa Rejoagung Kecamatan Ngoro Kabupaten Jombang) - Ummu Rofi’ah; Wakid Evendi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
In the customary practices of the Javanese Muslim society, there are often certain approaches employed to prevent divorces. This approach is commonly referred to as